On blowdown analysis with efficient and reliable direct time integration methods for wave propagation and fluid-structure-interaction response - Nilsson, Kenth; Tornberg, Fredrik (Computers & structures, 2019)
•Wave propagation and fluid-structure-interaction dynamic response.•Validation of iterative and direct fluid-structure-interaction CFD and FE models.•Efficiency, accuracy and reliability of time integration methods in linear and non-linear blowdown analyses.•Bathe time integration method. In literature time integration methods are described separately for wave propagation or structural dynamic problems. In this paper we focus on implicit methods for problems that involve simultaneous wave propagation and strong fluid-structure-interaction response. As example we show methods and models for nuclear pressure vessel blowdown analysis. We present validation against measurements from literature for three different ways to perform this analysis. These are: 2-way iterative fluid-structure-interaction (FSI) between CFD and FE codes, direct 2-way FSI in the FE code and sequential 1+2-way FSI. The CFD and FE codes provide different time integration methods. Here we investigate the trapezoidal and composite methods, in the FE code the Bathe method. We show that the selected validation problem is linear and follows the principle of superposition and can be solved with the all-linear fluid-structure FE model, with the trapezoidal rule for computational efficiency. On the contrary, in applied analyses of reactor pressure vessels structural non-linearities must often be included, such as contact, friction stick-slip and plasticity. We show that for non-linear fluid-structure FE models the Bathe method is efficient and reliable. The Bathe method provides high accuracy in both the wave propagation and the fluid-structure-interaction response.